The spooky cabin - Fruchter, Jason; Nickelodeon (Firm); Penguin Random House; Random House Children's Books; Spin Master (Firm) (New York Random House, 2017)
"The Paw Patrol visits a spooky old cabin"--Page [4] of cover
English Stories
2 13
Keywords: Dogs -- Fiction; Dogs -- Juvenile fiction; Dogs; Fear -- Fiction; Fear -- Juvenile fiction; Fear; Haunted houses -- Fiction; Haunted houses -- Juvenile fiction; Haunted houses; JUVENILE FICTION -- Action & Adventure; JUVENILE FICTION -- Animals -- Dogs; JUVENILE FICTION -- Media Tie-In; Radio and television novels; Rescue dogs -- Juvenile fiction; Rescue dogs; Dogs -- Fiction; Fear -- Fiction; Haunted houses -- Fiction; Rescue dogs -- Fiction; Fiction; Juvenile works; Readers (Publications); Readers (Publications); Juvenile works; Radio and television novels